Study on Attenuating Angiogenesis and Epithelial–Mesenchymal Transition (EMT) of Non-Small Cell Lung Carcinoma (NSCLC) by Regulating MAGEC2. (7th September 2018) - Jiang, Sicong; Liu, Xi; Li, Daojing; Yan, Meiying; Ju, Cheng; Sun, Jun; Jiang, Feng
Objective: To investigate the role of MAGE family member C2 in angiogenesis and epithelial–mesenchymal transition of non-small cell lung carcinoma. Methods: The Cancer Genome Atlas data set was analyzed to filter the highly expressed gene melanoma antigen family C2 in non-small cell lung carcinoma. Quantitative reverse transcription-polymerase chain reaction was performed to verify the overexpression of melanoma antigen family C2 in non-small cell lung carcinoma cell lines. Melanoma antigen family C2 complementary DNA and short hairpin RNA (shRNA) were transfected into SK-MES-1 cells to regulate melanoma antigen family C2 expression. Cell Counting Kit-8 assay, flow cytometry, wound healing assay, and Transwell assay were performed to investigate the effect of melanoma antigen family C2 on proliferation, apoptosis, migration, and invasion of SK-MES-1 cell line. Western blot was used to detect the expression of epithelial–mesenchymal transition markers. Enzyme-linked immunosorbent assay was performed to investigate the secretion of vascular endothelial growth factor, and tube formation assay was conducted to explore the effect of melanoma antigen family C2 on angiogenesis ability of the tumor. Tumor xenograft on nude mice and immunohistochemical/hematoxylin and eosin staining were also performed to detect the influence of melanoma antigen family C2 on growth and metastasis of non-small cell lung carcinoma cells. Results: Melanoma antigen family C2 was highly expressed in non-small cell lung carcinoma cells; melanoma antigen family C2 promoted the expression of epithelial–mesenchymal transition-related proteins as well as enhance the secretion of vascular endothelial growth factor and promote angiogenesis; melanoma antigen family C2 promoted proliferation, migration, and invasion and suppressed apoptosis of non-small cell lung carcinoma cells. It could also facilitate growth and metastasis of non-small cell lung carcinoma in vivo . Conclusion: Melanoma antigen family C2 was a critical factor of angiogenesis and epithelial–mesenchymal transition in non-small cell lung carcinoma.